Странности любви...: сборник / Л. А. Жуховицкий, В. А. Дорошенко, Л. А. Ямская - Жуховицкий Леонид Аронович (Молодая гвардия, 1991)
Экземпляры: ЧЗ (20160122) / Инвентарный номер: 30162 / Цена: 2.00 / Сис.шифр: 87.7 / Авт.знак: С 83 / ГРНТИ: 02 / ББК: 87.7